2015
DOI: 10.1177/0957650915617855
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the effects of wind shear coefficients on the flow characteristics of the near wake of a wind turbine blade

Abstract: This study investigates the effects of wind shear and wind shear coefficients on the near wake of a wind turbine. A wind turbine is subjected to the effects of wind shear, which leads to unsteady performance of the blade and characteristics of the blade near the wake. Wind shear coefficients of 0.1, 0.2, and 0.3 are used. The results are obtained using the three-dimensional incompressible Reynolds-Averaged Navier-Stokes equations, and the turbulence, are simulated via the shear-stress transport k–ω turbulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Formula (25) indicates that different wind speed model result in different wind farm power. Formulas (5) and (13) in section 2 show that the average wind speed of both WS model and TS model are less than uniform wind speed, and that means both WS and TS will result in wind farm power loss compared with power output in the case of uniform wind speed according to (25). This item of power loss is defined as wind farm loss.…”
Section: Power Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Formula (25) indicates that different wind speed model result in different wind farm power. Formulas (5) and (13) in section 2 show that the average wind speed of both WS model and TS model are less than uniform wind speed, and that means both WS and TS will result in wind farm power loss compared with power output in the case of uniform wind speed according to (25). This item of power loss is defined as wind farm loss.…”
Section: Power Lossmentioning
confidence: 99%
“…Some researchers studied WS and TS from the aspect of the wake of a wind turbine. Wang et al [13] studied the effects of WS and WS coefficients on the near wake of wind turbine and indicated that the torque of the blade as well as the characteristic of the blade near wake varied periodically due to WS. The axis, tangential, and radial velocities and the turbulence intensity were significantly affected by WS at the region of the blade near wake.…”
Section: Introductionmentioning
confidence: 99%
“…The computational domain used the structured hexahedral grid. The details of the computational domain for the Phase VI blade and the WindPACT blade, as shown in Figure 2, can be seen Wang et al 44,45 The total number of grid nodes was approximately 4.35 Â 10 6 (the Phase VI blade) and 5.15 Â 10 6 (the WindPACT blade). For the Phase VI blade, the chordwise and spanwise directions were meshed 200 and 129 nodes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the wind turbine drive torque, the pitch bending moment, and the yaw moment, and so on, will change accordingly. The wind speed spatiotemporal distribution characteristics directly affect the aerodynamic load resulting in load fluctuation of the WT [2][3][4]. Besides, it will also affect the power output of the wind turbine generator system (WTGS) [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%